The cape and other stories from the Japanese ghetto - Nakagami, Kenji (Berkeley, Calif. : Stone Bridge Press, 1976)
Anguished, lusty, tragic, brutal...are the stories and setting of this collection from one of Japan's great postwar literary masters. Kenji Nakagami was born a burakumin. Isolated in the same rural and urban ghettoes for centuries, the burakumin are Japan's little-known outcaste class who still suffer subtle and not-so-subtle acts of discrimination and abuse.
Nakagami's breakthrough work, The Cape portrays a tough burakumin family, scarred by violence, held together by courage and love, yet threatened by madness and one man's tormented musings on the father he barely knew. In House on Fire, the phenomenon of generational violence plays out in the character study of an ordinary man trapped by his memories and an unfathomable rage. Red Hair is an extended erotic dream, an accidental carnal interlude between a working-class man and a mysterious woman who escape together into the comfort and torture of pure physicality.
Driven by full-bodied characters and muscular prose, Nakagami's stories unveil the disturbing landscapes and alleyways he knew all too well.